2008
DOI: 10.1007/s10886-008-9566-4
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone Disruption of Argentine Ant Trail Integrity

Abstract: Disruption of Argentine ant trail following and reduced ability to forage (measured by bait location success) was achieved after presentation of an oversupply of trail pheromone, (Z)-9-hexadecenal. Experiments tested single pheromone point sources and dispersion of a formulation in small field plots. Ant walking behavior was recorded and digitized by using video tracking, before and after presentation of trail pheromone. Ants showed changes in three parameters within seconds of treatment: (1) Ants on trails no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 31 publications
7
63
3
Order By: Relevance
“…This is an improvement in longevity of disruption over the wax-based dispersible formulating originally tested, which disrupted visual trails and foraging at bait cards in 4-m 2 plots for only 24 h (Suckling et al 2008). We also were able to demonstrate significant disruption of foraging by Argentine ant workers for bait cards.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…This is an improvement in longevity of disruption over the wax-based dispersible formulating originally tested, which disrupted visual trails and foraging at bait cards in 4-m 2 plots for only 24 h (Suckling et al 2008). We also were able to demonstrate significant disruption of foraging by Argentine ant workers for bait cards.…”
Section: Discussionmentioning
confidence: 58%
“…Our bioassay that examined traffic rates proved to be a robust and reliable measure of trail disruption from a point source (Suckling et al 2008;Tanaka et al 2009). The results showed that the treated bioassay cards, stored in the absence of sunlight or rainfall, maintained their efficacy at disrupting trail following for many weeks.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For detection, pyrazine lures may have advantages over the commonly used peanut butter baits in that they may be more species-specific, longer lasting, more easily packaged, mess-free in application, and less prone to spoil. Potential control applications of W. auropunctata pheromones include use in insecticidal baits to increase feeding (Hughes et al, 2002) and direct disruption of ant behavior, similar in concept to pheromone mating disruption (Suckling et al, 2008). Further testing in the field will be required to assess the potential of these possible applications.…”
Section: Discussionmentioning
confidence: 99%